1977
DOI: 10.1007/bf02586688
|View full text |Cite
|
Sign up to set email alerts
|

Combined therapy for cancer of the anal canal

Abstract: We believe this preoperative combined therapy is highly effective in treating squamous-cell carcinoma of the anal canal, and that a subsequent larger cooperative study with controls is indicated. This pilot study suggests that some individuals may be spared abdominoperineal resection when treated in the manner described.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

1981
1981
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(22 citation statements)
references
References 2 publications
0
21
0
1
Order By: Relevance
“…The surgical specimens of two patients showed no evidence of residual disease, whereas a third patient refused surgery and remained disease-free. Further experience from this group and other investigators reported similar high rates of clinical and pathologic response using preoperative chemoradiotherapy and surgery [3][4][5][6][7]. These results led to multiple phase 2 trials evaluating RT alone or combined chemoradiotherapy as "defi nitive" therapy.…”
Section: Anal Canal Squamous Cell Carcinoma: the Pastmentioning
confidence: 63%
“…The surgical specimens of two patients showed no evidence of residual disease, whereas a third patient refused surgery and remained disease-free. Further experience from this group and other investigators reported similar high rates of clinical and pathologic response using preoperative chemoradiotherapy and surgery [3][4][5][6][7]. These results led to multiple phase 2 trials evaluating RT alone or combined chemoradiotherapy as "defi nitive" therapy.…”
Section: Anal Canal Squamous Cell Carcinoma: the Pastmentioning
confidence: 63%
“…In Nigro's paper of 21 patients treated with 30 Gy in 15 fractions combined with MMC and 5-FU followed by surgery, 57% of patients had significant downstaging or no tumour at the time of Treatment of anal cancer in the elderly N Charnley et al surgery (Buroker et al, 1977). A subsequent report of 45 patients treated with the same regimen led to 84% having complete response and 89% remaining disease-free at a median follow-up of 50 months (Leichman et al, 1985).…”
Section: Discussionmentioning
confidence: 99%
“…The combination 5-FU and mitomycin with radiotherapy was used successfully for the treatment of squamous cell cancer of the anus 1,3,6 and later applied to carcinoma of the esophagus. Steiger et al administered 5-FU and mitomycin concurrently with 30 Gy prior to esophagectomy and found a median survival of 18 months and a complete pathologic response of 25%.…”
Section: Discussionmentioning
confidence: 99%
“…Favorable results of radiotherapy and infusional 5-fluorouracil (5-FU) combined with mitomycin in the treatment of squamous anorectal cancers [1][2][3] led to application of similar combined modality treatment for esophageal cancers. Radiotherapy doses of 30 gray (Gy) administered with two cycles of 5-FU and mitomycin produced local control and long term survival comparable with many surgical series.…”
Section: Conclusion High Dose Radiation Therapy With Concurrent 5-fmentioning
confidence: 99%